The Relationship Between Sleep Quality and Blood Pressure in Students - Muhammad Irwan; Irfan Irfan; Evawaty Evawaty; Rahmin Rahmin; Risnah Risnah; Salmah Arafah (Journal of Public Health and Pharmacy, 2024)
Introduction: Sleep is one of the physiological needs that has an impact on the quality and balance of life. The habit of poor sleep quality or a short amount of sleep is also associated with an increase in an individual's blood pressure. If someone's sleep duration is short, the sympathetic nervous system activity will increase, making the person vulnerable to stress, ultimately leading to an increase in blood pressure. Poor sleep quality and quantity not only causes physical discomfort, but also impairs individual memory and cognitive abilities. If this poor quality and quantity of sleep is left unattended for several years, more dangerous complications are likely to occur, such as heart attacks, strokes and psychological problems (such as depression or other mood disorders). The purpose of the study was to determine the relationship between sleep quality and blood pressure in final semester students of the Faculty of Health Sciences, Universitas Sulawesi Barat. Methods: The study used a cross-sectional approach. The number of samples of 45 respondents was selected by simple random sampling technique Results: The results of the chi-square test showed that there was no relationship between sleep quality and blood pressure (p>0.1). Conclusion: there is no significant relationship between sleep quality and blood pressure in students of the Faculty of Health Sciences in the Final Semester of the Universitas Sulawesi Barat.